(untitled) (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2025)
The increasing demand for chicken meat in Indonesia has encouraged the development of superior local chickens such as IPB D1, which have the ability to utilize local feed and exhibit rapid growth. This study aimed to determine the role of zinc, chromium, and lemuru oil supplementation on the digestive system development and internal organs functionality of IPB D1 chickens. A total of 100 twelve-weekold IPB D1 chickens were assigned to four treatment groups: control (P0), feed supplemented with zinc and chromium (P1), feed supplemented with lemuru oil (P2), and feed supplemented with zinc, chromium, and lemuru oil (P3). A Completely Randomized Design (CRD) was applied, and significant differences were analyzed using Tukey’s post hoc test. The findings revealed no significant impact of supplementation on the relative length of the digestive tract. Nonetheless, a significant increase in the percentage of gallbladder weight was observed in the P3 group (0.09%–0.13%). In contrast, the heart weight percentage was significantly reduced compared to the control group (0.48%–0.58%). These results indicate that combined supplementation of zinc, chromium, and lemuru oil may modulate lipid metabolism and cardiovascular function in IPB D1 chickens. Further investigations are required to establish optimal dosages and assess the long-term implications on the performance of IPB D1 chickens.